1992
DOI: 10.1083/jcb.118.5.1223
|View full text |Cite
|
Sign up to set email alerts
|

Association of intercellular adhesion molecule-1 (ICAM-1) with actin-containing cytoskeleton and alpha-actinin.

Abstract: We have studied the cytoskeletal association of intercellular adhesion molecule-1 (ICAM-1, CD54), an integral membrane protein that functions as a counterreceptor for leukocyte integrins (CD11/CD18). A linkage between ICAM-1 and cytoskeletal elements was suggested by studies showing a different ICAM-1 staining pattern for COS cells transfected with wild-type ICAM-1 or with an ICAM-1 construct that replaces the cytoplasmic and transmembrane domains of ICAM-1 with a glycophosphatidylinositol (GPI) anchor. Wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
186
0
3

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 279 publications
(194 citation statements)
references
References 58 publications
5
186
0
3
Order By: Relevance
“…Leukocyte TEM is inhibited after the inactivation of endothelial cells' Rho protein function (Adamson et al, 1999), thereby suggesting a proactive role for ICAM-1 signaling/cytoskeletal interactions in facilitating TEM. In agreement with these lines, the intracellular domain of ICAM-1 can bind to a variety of molecules, such as ␣-actinin (Carpen et al, 1992), ␤-tubulin, GAPDH (Federici et al, 1996), and ezrin (Heiska et al, 1998). These proteins all have the potential to perform signaling functions.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Leukocyte TEM is inhibited after the inactivation of endothelial cells' Rho protein function (Adamson et al, 1999), thereby suggesting a proactive role for ICAM-1 signaling/cytoskeletal interactions in facilitating TEM. In agreement with these lines, the intracellular domain of ICAM-1 can bind to a variety of molecules, such as ␣-actinin (Carpen et al, 1992), ␤-tubulin, GAPDH (Federici et al, 1996), and ezrin (Heiska et al, 1998). These proteins all have the potential to perform signaling functions.…”
Section: Introductionmentioning
confidence: 74%
“…Earlier reports have demonstrated that native ICAM-1 protein is associated with the actin-containing microfilament network and that their interaction is mediated by the cytoplasmic or transmembrane domains of ICAM-1 (Carpen et al, 1992;Carman et al, 2003). ICAM-1 has also been known to be associated with ezrin/radixin/moesin (ERM) family members, i.e., ezrin and moesin (Heiska et al, 1998;Barreiro et al, 2002).…”
Section: The Distribution and Dynamic Movements Of Icam-1 On Transfecmentioning
confidence: 99%
See 1 more Smart Citation
“…The requisite first step involves the low-affinity "rolling" of the leukocyte on the endothelium through the engagement of selectins (E-, P-, and L-selectin) with their ligands, PSGL-1 and sialyl LewisX, followed by a high-affinity "firm" adhesion mediated by leukocyte integrins binding to the endothelial intercellular adhesion molecule (ICAM-1) (Alon et al, 2003). The cytoplasmic domains of the integrins, selectins, and ICAM-1 are linked to the cytoskeleton through adapter actin-binding proteins, allowing for direct associations between integrins and cytoskeletal function (Sampath et al, 1998;Yoshida et al, 1996;Carpen et al, 1992). The intracellular mechanisms by which Slit negatively regulated leukocyte-endothelial dynamics in the cerebral microcirculation was not investigated in the present study, but available evidence supports the following sequence of events: Slit interaction with the extracellular domain of its single transmembrane domain receptor Robo promotes an association of the Slit-Robo complex with a novel family of Rho GTPase-activating proteins (GAPs) forming Slit-Robo GAPs (srGAPs) (Wong et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this group appears to be extremely ancient, as is evidenced by the recent discovery of Ig/tyrosine kinase receptors in animals as primitive as sponges (Schaecke et al, 1994). Many Ig superfamily receptors do not contain tyrosine kinase domains, however, and several have been found to possess cytoplasmic domains belonging to the family of protein tyrosine phosphatases (Krueger & Saito, 1992) or to possess short cytoplasmic tails that do not exhibit intrinsic activities but which are required for binding to other cytoplasmic functional proteins such as a-actinin (Carpen et al, 1992), actin (Letourneau & Shattuck, 1989), and spectrin (Pollenberg et al, 1987). Other Ig superfamily members, such as the memReprint requests to: Thomas P. Hopp brane forms of Igs themselves, possess cytoplasmic domains of only one or several amino acids and rely on other transmembrane proteins for signal transduction (Keegan & Paul, 1992).…”
mentioning
confidence: 99%